(untitled) (Research, Society and Development, 2020)
The main category of solid waste is construction and demolition waste, important due to the high volume and mass production. In this study, the objective is to develop an overview of the feasibility of implementing RCD in civil construction in the city of Campina Grande - PB. A survey was carried out through a questionnaire with students from the civil engineering course and a company in the civil construction sector, analyzing their knowledge regarding the production of RCD in the city, recycling of waste and the implementation of sustainable measures in this area. The results of the questionnaire confirm the diffusion of the theme among the students, but it demonstrates the need to approach companies that use RCD in their constructive practices. The evaluated company affirms its conscience on the subject and declares that the companies in the sector are oriented to the reuse of this waste. Therefore, it is necessary to talk about sustainable companies during classes and seminars at universities in order to encourage future entrepreneurs in the construction industry to implement sustainable measures.